Metagenomic Analysis of Dental Plaque on Pit and Fissure Sites With and Without Caries Among Adolescents - Pang, Liangyue; Wang, Yinuo; Ye, Yun; Zhou, Yan; Zhi, Qinghui; Lin, Huancai (Frontiers in Cellular and Infection Microbiology, 2021)
Caries is one of the most prevalent infectious diseases worldwide and is driven by the dysbiosis of dental biofilms adhering to tooth surfaces. The pits and fissured surfaces are the most susceptible sites of caries. However, information on the taxonomic composition and functional characteristics of the plaque microbiota in the pit and fissure sites is very limited. This study aimed to use metagenomic sequencing analyses to investigate the relationship between the plaque microbiome in the pit and fissure site and surface caries in adolescents. A total of 20 adolescents with severe pit and fissure surface caries were involved as well as 20 age-matched, caries-free teenagers for control tests. Plaque samples were collected from the pit and fissure site and were subjected to metagenomic analyses, in which the microbial communities were investigated. Our results showed that the microbiota diversity was similar between those two groups. At the species level, the relative abundances of A. gerencseriae, P. acidifaciens, P. multisaccharivorax, S. oralis, S. mutans and P. denticolens were higher in the caries active group. N. elongata, C. hominis and A. johnsonii were relatively more abundant in the caries-free groups. Functional analysis suggested that the metabolic pathway was the most abundant pathway, and the functional traits of the level 2 pathways included amino acid metabolism, metabolism of cofactors and vitamins and carbohydrate metabolism. Our results also revealed that the caries group displayed several alterations in metabolic pathways, including enriched functions in carbohydrate digestion and absorption. This study suggested that in addition to the specific anatomical structures of the pit and fissured surfaces, the fundamental differences in the plaque microbiome may also be related to the susceptibility of pit and fissure caries.